Keselamatan dan Kesehatan Kerja bagi Penambang Pasir di Desa Watudambo Dua, Minahasa Utara - Syanne Pangemanan; Jeanely Rangkang (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Negeri Manado, 2022)
Today's infrastructure development in North Sulawesi Province greatly influences and changes the socio-economic conditions of the surrounding community due to the opening of job opportunities. The need for building materials used in construction is very high. Mining minerals in North Minahasa Regency are types of industrial minerals such as stone, sand and stone / gravel. One type of mineral that is widely cultivated by community groups is sand mining. This research is a descriptive study with a quantitative approach to documentation and interviews. The research subjects were the village government, land owners and mining workers. Based on the results obtained on the activities of mining workers for the application of occupational safety and health, it is in the poor category. Barriers that affect the implementation of K3 include the lack of awareness of the importance of K3 and no special costs for the procurement of personal protective equipment (PPE). Efforts have been made to overcome these obstacles, namely by introducing knowledge and technology on the importance of K3 in carrying out sand mining work